2017
DOI: 10.1063/1.4983031
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric and piezoelectric properties of Hf1-xZrxO2 and pure ZrO2 films

Abstract: Ferroelectric and piezoelectric properties of Hf1-xZrxO2 (HZO) and pure ZrO2 films with a layer thickness of up to 390 nm prepared by chemical solution deposition (CSD) are investigated. The piezoelectric properties are measured using a double-beam laser interferometer (DBLI) and piezoresponse force microscopy. It is shown that for 100 nm thick films, the maximum remanent polarization is found for pure ZrO2 and reduces for the increasing hafnium content. A stable remanent polarization of 8 μC/cm2 is observed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
113
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 44 publications
5
113
0
1
Order By: Relevance
“…The 100, 200, and 500 nm-thick films exhibit almost the same d 33 in both pristine and cycle state. The absolute values are about 30% smaller than for the 1 μm-thick film, which again might be due to the slightly better average orientation of the thickest film.The order of magnitude of the effective d 33 as well as the observation of the decrease in displacement is in agreement with the earlier results ranging from 1 to 10 pm V À1 [1,17,42,43] (Starschich et al [17] quantified 10 pm V À1 for a unipolar measurement, whereas their Figure 2 suggests 20 pm V À1 for the pristine and 5 pm V À1 for the fatigued case of a bipolar large-signal measurement). Nonetheless, this behavior requires further studies, and CSD films do not endure as many switching cycles as their ALD or PVD counterparts (10 5 -10 11 depending on the frequency Figure 1. a) GIXRD patterns (log scale) of the 45 nm-thick La:HfO 2 thin films compared with the reference patterns from powder diffraction files (m, o, and c indicate the monoclinic, orthorhombic, and cubic phase, respectively); b) corresponding characteristics of polarization P versus electric field E; c) remanent polarization P r and relative permittivity ε r for different La contents.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…The 100, 200, and 500 nm-thick films exhibit almost the same d 33 in both pristine and cycle state. The absolute values are about 30% smaller than for the 1 μm-thick film, which again might be due to the slightly better average orientation of the thickest film.The order of magnitude of the effective d 33 as well as the observation of the decrease in displacement is in agreement with the earlier results ranging from 1 to 10 pm V À1 [1,17,42,43] (Starschich et al [17] quantified 10 pm V À1 for a unipolar measurement, whereas their Figure 2 suggests 20 pm V À1 for the pristine and 5 pm V À1 for the fatigued case of a bipolar large-signal measurement). Nonetheless, this behavior requires further studies, and CSD films do not endure as many switching cycles as their ALD or PVD counterparts (10 5 -10 11 depending on the frequency Figure 1. a) GIXRD patterns (log scale) of the 45 nm-thick La:HfO 2 thin films compared with the reference patterns from powder diffraction files (m, o, and c indicate the monoclinic, orthorhombic, and cubic phase, respectively); b) corresponding characteristics of polarization P versus electric field E; c) remanent polarization P r and relative permittivity ε r for different La contents.…”
supporting
confidence: 91%
“…The result is a dominant monoclinic bulk-phase and diminished FE behavior. In contrast, Park et al [48] showed that the 390 nm-thick solution-deposited ZrO 2 films in the report of Starschich et al [17] exhibit a fine-grained microstructure with grain radii in the range of 10 nm. It was proposed that this is the reason why the diminishment of the FE properties with increasing film thickness was only very minor.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The observations are compared to the system (Hf,Zr)O 2 , which has a much wider concentration window to achieve a stable ferroelectric phase. Combining these observations with the effects of grain size [3,13] and oxygen vacancies [52] on phase stability as well as the occurrence of internal bias fields, it can be concluded that the Si:HfO 2 system is a rather fragile system. This is mainly due to the role of Si as a very efficient stabilizer of the tetragonal phase which partially closes the window for a stable FE phase opened by factors such as O vacancies and surface energy.…”
Section: Wwwadvelectronicmatdementioning
confidence: 94%
“…However, it does not necessarily imply that direct measurement is impossible. With the chemical solution deposition, fluorite‐structured ferroelectric oxide films with thickness up to 390 nm were fabricated . Therefore, direct measurement of Δ T or Δ S of doped HfO 2 or (Hf,Zr)O 2 thin films should be possible in the near future.…”
Section: Theoretical and Experimentally Observed δS Values And Appliementioning
confidence: 99%